Tradition and modernity side-by-side: experiential tourism among Quechua communities - Sotomayor, Sandra (2019)
Experiential tourism can be a catalyst for enhancing the wellbeing of indigenous communities. Yet, experiential tourism is a conundrum as cultural adaption to increase tourists’ satisfaction can threaten authenticity. This study examined the dialectic between experiential tourism and traditional culture among seven Quechua communities in Peru offering experiential tourism, by addressing three questions: (1) What is the perceived the role of ancestral traditions in experiential tourism? (2) To what extent modernism permeates into their lifestyles?, and (3) How do they negotiate ancestral traditions and modernism? Data collected in 2015 revealed that locals involved in tourism considered a priority to keep their ancestral traditions alive by passing them on to new generations; those not involved in tourism are less compliant of cultural authenticity. As a result, study communities showed signs of acculturation, syncretism and re-authentication. Findings also revealed that tourism is perceived as the catalyst for keeping and recovering traditional cultural manifestations, while modernism of certain practices is a necessity. This study contributes to the tourism scholarship by stressing the necessity to negotiate the coexistence of modernity and traditions in experiential tourism. Findings also elucidate policy and marketing suggestions to increase the positive effect of experiential tourism in heritage preservation.